2020
DOI: 10.21272/mmi.2020.3-08
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Innovativeness: a Literature Review

Abstract: This paper reports the results of a systematic review of recent literature on consumer innovativeness. The main purpose of the research is to identify the current research themes, understand emerging themes, and predict future directions in consumer innovativeness research. Previous reviews were either narrowly scoped or needed to be updated. Accordingly, the current literature review may fill this gap in the literature. The study sample is 188 articles published in journals indexed in the Web of Science datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In accordance with Rogers' (2003) theory of diffusion of Innovation, he defines innovativeness as the degree to which a person is a pioneer in the adoption of new ideas and innovation products in comparison to other members of the system. Meanwhile, according to the results of the content analysis by Eryigit (2020) on the consequences of consumer innovativeness, various past studies suggest that a range of dependent variables were focused on buying intention, adoption, repurchase intention, brand loyalty, brand switching, perceived value, evaluation of product qualities, perceived risk, brand extension, and willingness to pay. The effects of consumer innovativeness toward adoption behaviour or intention have received the greatest attention (Eryigit, 2020).…”
Section: Literature Review Consumer Innovativeness As a Personal Factormentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with Rogers' (2003) theory of diffusion of Innovation, he defines innovativeness as the degree to which a person is a pioneer in the adoption of new ideas and innovation products in comparison to other members of the system. Meanwhile, according to the results of the content analysis by Eryigit (2020) on the consequences of consumer innovativeness, various past studies suggest that a range of dependent variables were focused on buying intention, adoption, repurchase intention, brand loyalty, brand switching, perceived value, evaluation of product qualities, perceived risk, brand extension, and willingness to pay. The effects of consumer innovativeness toward adoption behaviour or intention have received the greatest attention (Eryigit, 2020).…”
Section: Literature Review Consumer Innovativeness As a Personal Factormentioning
confidence: 99%
“…Meanwhile, according to the results of the content analysis by Eryigit (2020) on the consequences of consumer innovativeness, various past studies suggest that a range of dependent variables were focused on buying intention, adoption, repurchase intention, brand loyalty, brand switching, perceived value, evaluation of product qualities, perceived risk, brand extension, and willingness to pay. The effects of consumer innovativeness toward adoption behaviour or intention have received the greatest attention (Eryigit, 2020). Mangafić et al (2017); Wang (2014) concluded that consumer innovativeness is the crucial indicator for the adoption of innovative products.…”
Section: Literature Review Consumer Innovativeness As a Personal Factormentioning
confidence: 99%
“…We also examine consumer technology innovativeness as a personal trait moderator, which impacts how consumers perceive VA usefulness. Tech innovators readily embrace new technologies, while nontech innovators are more cautious (Eryigit, 2020). Thus, we investigate how the process and outcome quality of VAs influence VA usefulness based on consumers' technology innovativeness.…”
Section: Sjmementioning
confidence: 99%
“…Consumer innovativeness significantly impacts technology adoption (Eryigit, 2020). It refers to an individual's autonomous ability to assimilate new knowledge and make innovative judgments (Midgley and Dowling, 1978).…”
Section: The Role Of Technology Innovativenessmentioning
confidence: 99%
“…Numerous research in the academic literature have studied and attempted to clarify the notion of innovativeness, which is defined as the process of creating new ideas, products, and activities (Chao, Hung & Sun, 2022, Delorme et al, 2021, Li, Wang & Liao et al, 2021, Eryigit 2020 & Schillo, 2017, Park & Dyer, 1995. The idea of innovativeness has been described in a number of different ways.…”
Section: Consumer Innovativenessmentioning
confidence: 99%